ANALYSIS OF THE EFFECTIVENESS OF WATER HUFF AND PUFF TECHNOLOGY BASED ON GLOBAL APPLICATION EXPERIENCE AND LABORATORY RESEARCHES - Oleg I.Tsykunov; Ilya S. Kaeshkov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
The relevance. Today, a large number of oil fields with hard-to-recover reserves, in particular, with low-permeability reservoirs, are in exploration. With a permeability of less than 1 mD, the formation pressure flow system has low efficiency, and production wells have high decline rates and low flow rates even in the presence of hydraulic fracturing. A new technology, water Huff and Puff, can help solve this problem. This technology is a cyclic water injection, shutdown and subsequent withdrawal of fluid during an oil well production. It allows us to initiate the process of capillary imbibition in marginal waterless wells in a low-permeability reservoir and increase oil production. The main aim: to analyze the world experience in the application and laboratory studies of the Huff and Puff technology, to determine the key parameters of its effectiveness, to formulate criteria for the applicability of the technology. Objects: capillary imbibition in a low-permeability oil-saturated reservoir, the results of laboratory studies, reports on the application of the technology in oil fields. Methods: evaluation and analysis of existing laboratory studies of technology on core, analysis of the conditions and methods for conducting experiments and their results, comparison with similar studies, identification of common dependencies; review of the experience of applying the technology in the USA, China and Russia, comparing their results with the results of laboratory studies. Results. During the analysis of laboratory studies, the key parameters of the effectiveness of the technology application – the presence of fractures in the reservoir, low permeability, hydrophilicity and small characteristic size of pore channels – were identified. An analysis of the world experience in the use of water Huff and Puff showed that the technology is successfully used in China in low-permeability hydrophilic formations in wells with multi-stage hydraulic fracturing, which is confirmed by laboratory studies. The US experience has not been successful due to the hydrophobicity of the reservoirs. The experience in Russia has mixed results – due to the hydrophilicity and low permeability of the reservoir, the effect of capillary impregnation is present, but due to the design of the wells and the absence of open hydraulic fractures, there was no significant effect. The results of the application experience are consistent with laboratory test data. As a result of this analysis, criteria for the applicability of water Huff and Puff technology were formed.